PERILAKU BULLYING DI KALANGAN PELAJAR - Emanuel Haru (Jurnal Alternatif Wacana Ilmiah Interkultural, 2022)
Bullying is a form of violent behavior that often occurs among students. This article aims to discuss the phenomenon of bullying among students. There are several formulations of the problem posed. First, what are the forms of bullying among students? Second, what factors cause bullying among students? Third, what are the impacts caused by bullying among students? Fourth, what are the strategies used to overcome bullying among students? By using the literature study method, including reviewing research findings regarding the bullying phenomenon, the writer concludes. First, the forms of bullying among students are verbal, physical, social, cyber and sexual bullying. Second, the factors that influence bullying are distinguished between internal and external factors. Internal factors are related to the individual factors themselves in the form of introverted personality and wrong self-concept. While external factors in the form of family, school, peers, mass media. Third, the effects of bullying can occur for both victims and perpetrators. For victims, the impact occurs physically and psychologically. As for the perpetrator, the act of bullying that he does makes him a person who is not empathetic, considers this action as normal and becomes a perpetrator of a criminal act. Fourth, several strategies were implemented to prevent and overcome bullying among students are exploring the root causes of bullying, giving punishments, forming study groups, providing advice and adequate information about bullying, running a "stop bullying" program and supervising.